PENERAPAN LANGUAGE EXPERIENCE APPROACH UNTUK MENINGKATKAN KETERAMPILAN MENULIS SISWA KELAS V SDN 105292 BANDAR KLIPPA T.A 2023/2024 - Simanjuntak, Reni Violina; Faisal, F; Nurmayani, N; Halimatussakdiah, Dr.; Sirait, Albert Pauli (Universitas Negeri Medan, 2024)
This research aims to describe the planning, describe the implementation, and the results of implementing the Language Experience Approach in improving students' writing skills. This type of research is Classroom Action Research which was carried out in class V A of SDN 105292 Bandar Klippa with a total of 30 students. The time for carrying out this research was in the even semester of T.A. 2023/2024. The data collection techniques used were interviews, tests and non-tests (observation and documentation). The students' pre-cycle writing results got an average score of 56. After being given the Language Experience Approach action in cycle 1 for lesson planning, meeting I got a score of 78.82% and meeting II got a score of 81.17%, for observing learning activities the teacher got a score of 65 % in meeting I and 75% in meeting II, for activities students got a score of 67.5% in meeting I and 75% in meeting II, students' writing results increased with an average score of 71.17. Then continued with cycle II, for lesson planning the first meeting obtained a score of 88.23% and the second meeting received a score percentage of 91.67%, for observation of learning activities the teacher received a score of 83.75% in the first meeting and 95% in the second meeting, while for Student activities scored 85% in meeting I and 90% in meeting II and students' writing results increased with an average score of 82.83. From these results it can be concluded that there was an improvement after implementing the Language Experience Approach in the writing skills of class V students at SDN 105292 Bandar Klippa T.A 2023/2024.Keywords: Writing Skills, Language Experience Approach